METODE SMALL SIDED GAMES UNTUK MENINGKATKAN HASIL BELAJAR KETERAMPILAN CHESTPASS BOLA BASKET PADA ANAK - Muhammad Ashfahany Arya Hindrian; Hariyoko; Muhammad Iqbal Jauhar Hanim (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study was conducted due to the low achievement of chest passing learning outcomes in academy sahabat ponorogo consisting of 24 students with 10 female students and 14 male students. The purpose of this study was to improve the learning outcomes of chest passing with the application of the Small Sided Games method. Sports Action Research conducted is a collaboration between researchers and coaches. The research was conducted in 2 cycles, each consisting of 3 meetings, with each cycle going through the stages of planning, implementation, observation, and reflection. This study used several instruments, namely using the Lehsten basketball test and process assessment sheet and using free scale norms. Data analysis in this study is using qualitative and quantitative analysis methods. The results showed that there was an increase in the completeness of each student's chest passing process, in the pre-cycle showed 33.33%, then increased in cycle I by 79.17% and in cycle II increased again to 91.67%. In the overall chest passing process assessment, it reached a score of 104 out of 120 maximum scores with a completion percentage of 86.67%. While the completeness of the results assessment is to reach a score of 171 out of a maximum score of 240 with a percentage of 71.25%. With these results, the completeness of the process assessment of each student is in the excellent classification, the completeness of the overall process assessment is in the good classification, and the results assessment is in the sufficient classification.